2020
DOI: 10.1016/j.isci.2020.101704
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Inventory of Intermediate Metabolites of Cyanobacteria in a Diurnal Cycle

Abstract: Cyanobacteria are gaining importance both as hosts for photoautotrophic production of chemicals and as model systems for studies of diurnal lifestyle. The proteome and transcriptome of cyanobacteria have been closely examined under diurnal growth, whereas the downstream effects on the intermediary metabolism have not received sufficient attention. The present study focuses on identifying the cellular metabolites whose inventories undergo dramatic changes in a fast-growing cyanobacterium, Synechococcus elongatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 72 publications
(117 reference statements)
1
28
0
Order By: Relevance
“…This method is now well established for the detection and quantification of charged and polar metabolites (Jaiswal et al, 2020a;Mccloskey and Gangoiti, 2015). Ten γ-glutamyl dipeptides and the reduced and oxidized forms of glutathione (GSH and GSSG, respectively) were readily identified using the MetDIA and MS-DIAL metabolite identification tools (Li et al, 2016;Tsugawa et al, 2015), as has been reported previously (Table 1) (Jaiswal and Wangikar, 2020a). A few additional dipeptides, such as γ-glutamyl tryptophan, were identified based on MS1 matches followed by matching the fragmentation pattern.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…This method is now well established for the detection and quantification of charged and polar metabolites (Jaiswal et al, 2020a;Mccloskey and Gangoiti, 2015). Ten γ-glutamyl dipeptides and the reduced and oxidized forms of glutathione (GSH and GSSG, respectively) were readily identified using the MetDIA and MS-DIAL metabolite identification tools (Li et al, 2016;Tsugawa et al, 2015), as has been reported previously (Table 1) (Jaiswal and Wangikar, 2020a). A few additional dipeptides, such as γ-glutamyl tryptophan, were identified based on MS1 matches followed by matching the fragmentation pattern.…”
Section: Resultsmentioning
confidence: 73%
“…The LC method was based on reverse-phase chromatography with tributylamine as the ion-pairing agent added in the mobile phase (Jaiswal et al, 2020a;Mccloskey and Gangoiti, 2015). This method is now well established for the detection and quantification of charged and polar metabolites (Jaiswal et al, 2020a;Mccloskey and Gangoiti, 2015). Ten γ-glutamyl dipeptides and the reduced and oxidized forms of glutathione (GSH and GSSG, respectively) were readily identified using the MetDIA and MS-DIAL metabolite identification tools (Li et al, 2016;Tsugawa et al, 2015), as has been reported previously (Table 1) (Jaiswal and Wangikar, 2020a).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Small changes in inactive pool sizes can result in large differences in absolute flux. Recent metabolomic studies confirm significant changes in intermediates across the diurnal cycle to maximize growth during the day ( Werner et al, 2019 ; Jaiswal and Wangikar, 2020 ). The ability to modulate the fractional size of active intermediates during different light conditions provide an additional means to control the rate of CBB cycle reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of regulation of the pigments are not clear and will require further investigation which is out of the scope of current study. Of interest will be to identify the metabolomic changes in the transformants (Hasunuma et al, 2013;Schwarz et al, 2013;Behrendt et al, 2018;Jaiswal and Wangikar, 2020) and how the variation in SbtA levels alter the bicarbonate uptake rates and intracellular labeling rates through 13C-metabolic labeling studies (Alagesan et al, 2013;Prasannan et al, 2019) as well as the proteomic changes in the transformants.…”
Section: Discussionmentioning
confidence: 99%